Dialysis catheter malfunction - Marques,Maria G (2017)
Vascular access is a crucial factor in the treatment of hemodialysis patients. Dialysis catheters are associated with higher mortality than fistulas, meaning they should be the last choice for most patients. Although they have many drawbacks, catheters play an important role in providing a reliable vascular access in some patients. Dialysis catheter dysfunction is a major cause of morbidity. Early dysfunction usually occurs as a result of mechanical issues while late dysfunction is most commonly due to thrombosis. The causes of dysfunction and their management are distinct, and understanding of them is essential to preserve catheter patency and improve dialysis patient outcomes